Presentation of a clinic case: asymptomatic rhinolithiasis in a nine-year-old chid - Mendes, Yanne; Sales, Elaine Oliveira; Polizzi, Lígia Oliveira; Mendes, Luciene Dornas; Greco, Alexandre Camisassa Diniz Leite; Azevedo, Carolina Drumond de Barros e; Manzi, Flávio Ricardo (Journal of Oral Diagnosis, 2018)
Introduction: Rhinolith is a petrea formation, relatively uncommon, which develops itself in the nasal cavity and it is rarely asymptomatic. It is formed from the deposition of or- ganic and inorganic compounds,on a foreign body and it can initiate symptoms like runny nose, nasal obstruction, foul odor and epistaxis. As the rhinolith has evoluted, it can bring more grave complications as oronasal perforation and nasal septum deviation. The choice treatment is usually based on the surgical removal of the calcified mass. Objetive: This study aims at relating a rare case of asymptomatic rhinolithiasis accidentally diagnosed in the left nasal cavity of a 9-year-old child. Case Report: Male patient, 9 years old, under a dental treatment was sent by the clinician for the image exams achievement aiming at visualizing a supernumerary tooth located on the anterior maxilla region promoting the 21 dental tooth migration. The patient was subjected to a Computed Tomography Cone Beam. It was observed, on this exam, the presence of a supernumerary tooth in formation, a calcified mass on nasal cavitys upper third on the left side, with dimensions of 1cm width and 1,5 cm height and depth, promoting partial obstruction of oropharynx on the left side. It was also observed, adenoid hypertrophy. Conclusions: The case related showed how important are the image exams to do the precise diagnosis on this pathology, in order not to pass unnoticed during many years, thus leading the patient future serious complications. The recognition of this entity in routine radiographs exams, by the dental surgeon it is of a great importance for to the precosis diagnosis and tratment.